Salient Conclusive Remarks on Epidemiology and Clinical Manifestations of Pediatric COVID-19: Narrative Review - Ali, Abdelwahid Saeed; Al-Hakami, Ahmed Mossa; Shati, Ayed Abdullah; Asseri, Ali Alsuheel; Al-Qahatani, Saleh Mohammed (Frontiers in Pediatrics, 2020)
The ongoing pandemic of COVID19, which caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), constitutes significant health concerns as impacting the human populations worldwide. In this scientific communication, a narrative review study was performed to shed some lights on the characteristic epidemiological features and clinical phenotypes of COVID19 reported for pediatric patients globally. Although some similar pediatric reports had seen in the literature, we still believe that the epidemiology and pathology of the infection among pediatric patients is unclear and not conclusive. We also believe that the novelty of our study resides in the summary for the elements concerning the age of infection, virus acquisition, explanations of the low infectivity rates, consequences of infections, and the discriminatory clinical manifestations of the disease in children. The search included data published from the date of the pandemic started (December 2019) up to July 2020. Our findings indicated that all age groups of children including the neonates had been infected by the virus. The virus can induce pathology and patients manifest symptomatology of the disease with benign nature and low aggressiveness. Asymptomatic and symptomatic patients are the only source of the virus to the children in the vicinity. Intrauterine and breastfeeding infections to the neonates were hypothesized in some studies but ruled out since they were not confirmed. Intensive review and discussion warranting the low infection rates and benign conditions of COVID19 in children were also made in this study. Infectivity, morbidity and mortality rates of the disease in the children populations are much lower than those in adults. They also seen lower than those observed during SARS-CoV and MERS-CoV epidemics. Clinical phenotypes of COVID19 in children do not differ much from those of adults and complications seen associated with comorbidities.